On a clear April morning - Iolovitch, Marcos, -1984 (Jewish Latin American studies, 2020)
"On a Clear April Morning, by Marcos Iolovitch, is a lyrical and riveting coming of age story set among early twentieth-century settlers brought to an almost unknown Jewish farming experiment in an isolated corner of Brazil. This autobiographical novel is filled with drama, joy, disasters, romance, and humor. It travels from farms where the crops won't grow to towns where the Yiddish-speaking protagonist falls in love, befriends sons of German immigrants, studies philosophy with the Jesuits, and becomes an important member of Brazil's literary world. This first English edition includes elucidating historical notes on the origin of Jewish farming communities in the U.S., Canada and South America by the translator, Merrie Blocker, a retired U.S. Foreign Service officer"--